The Effect of Implementing Portal iHCMS on Employee Satisfaction Moderated by Electronic Service Quality - Ade Saepulloh; Rora Puspita Sari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The implementation of an information technology based human resource management system is a strategic element in improving the effectiveness of human resource management and employee satisfaction. This study aims to analyze the effect of the implementation of the iHCMS Portal on employee satisfaction with the quality of electronic services as a moderating variable. This study used 348 permanent employees of PT Biofarma as active users of the iHCMS Portal. Data were collected through online questionnaire and analyzed using Structural Equation Modeling Partial Least Squares (SEM PLS). The study’s result indicates that the implementation of Portal iHCMS has a positive and significant effect on employee satisfaction. In addition, the implementation of Portal iHCMS has a positive effect on the quality of electronic services, and the quality of electronic services has a significant effect on employee satisfaction. Other findings indicate that the quality of electronic services strengthens the relationship between the implementation of Portal iHCMS and employee satisfaction. The implementation of Portal iHCMS, both directly and indirectly through the moderating role of electronic service quality, has been shown to have a positive contribution to increasing employee satisfaction. This study provides recommendations for organizations to optimize the implementation of Portal iHCMS by ensuring adequate electronic service quality.